(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
WSN gained a lot of attention because they are small and economical devices with low power utilization, and finite computing resources are progressively being enfolded in various application situations, including environmental monitoring, reconnaissance tracking, and health monitoring. In many applications of this type, node localization is an intrinsic parameter of the system. To report events origin, routing, and network coverage (A&Q), assist group querying of the sensors Localization process is mandatory. Localization is categorized into two types, which are a range-based or range-free scheme which is further divided into two sub-schemes as a fully and hybrid. For the detailed analysis and study, we are going to investigate localization schemes based on static and mobile WSN in this work. This research opens the new paradigm and future planning for the localization algorithms mainly how sensors are deployed? What kind of measures are taken into account to boost the algorithms so that the system can calibrate itself in changing environments?